Begonia menggaensis (sect. Diploclinium, Begoniaceae), a new tuberous species from western Yunnan, China - Yu, Ming-Bin; Tian, Dai-Ke; Liu, Yuan; Tang, Zhong-Bing (Phytotaxa, 2026)
Begonia menggaensis, a new tuberous species of Begonia sect. Diploclinium (Begoniaceae) from western Yunnan of China, is described and illustrated. It is morphologically similar to both B. cangyuanensis and B. yui, but mainly lacks the stolons of the former and two bracteoles on pedicel under ovary in both species. The conservation status of the new species is provisionally assessed as Critically Endangered (CR) following The Guidelines for Using IUCN Red List Categories and Criteria.